Bimbingan dan Konseling Islam dengan Ĥalāqah Ta’līm dalam Meningkatkan Spiritualitas Mahasantri Ma’had al-Jami’ah UIN Raden Intan Lampung - Aulia, Shofia; Damayanti, Rika; Masya, Hardiyansyah (Study Program of Arabic Language Teaching, 2025)
This study analyzes the relationship between Islamic guidance and counseling (BKI) and the ḥalāqah ta'lim method to improve students' spirituality at Ma'had al-Jami'ah UIN Raden Intan Lampung. The research method used is qualitative research with a case study type. Data in the form of Islamic Guidance and Counseling service activities with Ḥalāqah Ta'lim in Improving the Spirituality of Students at Ma'had al-Jami'ah UIN Raden Intan Lampung obtained through observation techniques, in-depth interviews (with Ma'had administrators, ustadz/ustadzah, and students), and documentation. Data analysis was carried out through three stages: data reduction, data presentation, and conclusion. The study results indicate that the ḥalāqah ta'lim method, as one of the methods in Islamic guidance and counseling, plays a significant role in improving students' spirituality. The ḥalāqah ta'lim method can be an effective form of service because it includes important elements that align with Islamic counseling principles, such as spiritual guidance, character development, and improving the quality of individual life. The activities of the ḥalāqah ta'lim method, which include learning the Qur'an, learning English and Arabic, and moral development, can increase the spiritual awareness of Ma'had al-Jami'ah UIN Raden Intan Lampung students.